Математичне моделювання конкурентних процесів у нелінійних системах із взаємодією - Луханін, В. С. (ХНУРЕ, 2024)
Competition is a vital aspect of the economy and is extensively studied through mathematical models, despite the complexity of competitive systems. There aren't many mathematical models describing competitive processes, but since most models are universal, there is a sufficient set of them, each with its own advantages and disadvantages. They include Peter Lancaster's model, the Malthusian model, and also crucial models of mutualism between species. These mathematical models find applications across diverse fields like engineering, biology, demography, and economics.
Keywords: конкурентний процес; нелінійна система із взаємодією